Studies on Heterobinuclear Copper-Zinc Complexes of Amino Acids as Biomimic Systems of Superoxide Dismutase - Clament Sagaya Selvam, N.; Thinesh Kumar, R.; John Kennedy, L.; Judith Vijaya, J. (Asian Journal of Chemistry, 2011)
Superoxide dismutase (SOD) contains two metal ions Cu(II) and Zn(II), active sites being bridged by the imidazolate anion. A model system for this enzyme has been investigated by attempted syntheses of copper-zinc complexes of amino acids [CuZn(L1)4(H2O)2] where L1 = glycine and [CuZn(L2)3(H2O)2] where L2 = histidine. The characterization of these compounds was carried out by conductance measurements, electronic, electron paramagnetic resonance (EPR) spectroscopy, fourier transform infrared spectra (FT-IR) and cyclic voltammetry along with the catalytic decomposition of hydrogen peroxide. From the above studies, it is interesting to note that the complex [CuZn(his)3(H2O)2] alone forms a mixed metal complex, which mimics the native enzyme both structurally and spectroscopically whereas glycine complexes form only the mechanical mixture of CuL1 and ZnL1. The peculiar coordination behaviour of histidine is its ability to act as a bridging ligand between the two metal atoms through the nitrogen atoms of imidazolate anions as observed in the native superoxide dismutase enzyme.